Exclusive breast feeding practice and associated factors among Rural and Urban mothers of child aged 0–6 months in Tahtay Maichew District of Tigray, Ethiopia, 2023/2024: Comparative cross sectional study - Mebrahtom Birhane Tikue; Teklay Zeru Weldearegawi; Teklemariam Gebregziabher Goitom; Berhe Gebrehiwot Tewele; Nebiat Desale Gidey; Willi Bahre (PLoS ONE, 2026)
Background The most well- recognized method of feeding a baby is breastfeeding. Out of all the preventive measures, breastfeeding and supplemental feeding have the most impact on child mortality for infants and young children. Babies are shielded against acute infections by the mother’s antibodies found in breast milk, and it boosts a baby’s immune system, their reaction to immunizations and cognitive benefits. This was aimed to compare and identify the factors associated with exclusive breastfeeding practice among the rural and urban lactating mothers of the District. Exclusive breast feeding practice of this rural area was in line with the urban which was 68.1% (95% CI, 62.1–73) and 64% (95% CI, 53.5–74.4) respectively. This might be due to the similar primary health care policy intervention system both in the rural and urban areas of the Region. Besides of this, both the rural and urban mothers of the district were more benefited from the Ethiopia primary health care packages. Methods A comparative cross-sectional study was conducted. A total of 346 lactating mothers were enrolled for the study. 5 rural and 1 urban Kebeles were randomly selected. From these the simple random sampling technique was used. The interviewer administered structured questionnaire was employed. Epi-Data Manager Version 4.6 was used to enter, encode, and clean the data for consistency and completeness. The data was analyzed using SPSS version of 22. Bivariable and multivariable logistic regression analysis were performed. Results A total of 346 lactating mothers were selected in both rural (258) and urban (88) areas of the district. The response rate was 248 (96.12%) in rural and 86 (97.72%) in urban. The prevalence of exclusive breastfeeding practice in the rural and urban areas was 68.1% (95% CI, 62.1–73) and 64% (95% CI, 53.5–74.4), respectively. According to the multivariable logistic regression analysis, in the rural mothers’ educational status [AOR = 2.46, 95% CI (1.3–4.6)], parity [AOR = 2.56, 95% CI (1.4–4.7)], and antenatal care visit [AOR = 2.35, 95% CI (1.0–5.4)] were associated factors. In the urban area, education on exclusive breastfeeding practice during antenatal care visits [AOR = 3.46, CI (1.2–10)], mode of delivery [AOR = 3.7, CI (1.2–11.5)] and education on exclusive breast feeding practice during postnatal care visit [AOR = 2.9, CI (1.0–8.1)] were associated factors. Conclusion Based on the mean score, exclusive breastfeeding practice in the rural and urban areas was slightly above the mean. This result doesn’t show a significant difference both in the rural and urban areas. But this was lower than the notional and global recommendation level. It was substantially correlated with maternal educational status, parity, and prenatal care visits in the rural areas and with health education during prenatal care visits, method of birth, and postnatal care visits in the urban areas. Recommendation We recommend that health care policy makers and health care providers strengthen the delivery of health education about exclusive breastfeeding practice during ANC visits and PNC visits, and they should advocate institutional delivery. Secondly, mothers should attend ANC and PNC and conduct institutional delivery so as to get information about exclusive breastfeeding practice.